Analisa dan Perancangan Sistem Perhitungan Insentif Marketing Trade Menggunakan Sistem Remunerasi - Khoiriyah, Siti; Manikam, Ratna Mutu (Jurnal Pendidikan Informatika (EDUMATIC), 2019)
PT. Kobe Boga Utama is a company engaged in food manufacturing with trademarks such as Boncabe, Kobe Flour Seasoning, Oyster Sauce Taste, and so forth. Having many sales branches spread in various cities in Indonesia such as in Jakarta, Bandung, Palembang, Bali, and many other cities. In the trade marketing department, the calculation and recording of incentives are still manual, which often results in data loss, data mismatch, delays in calculating incentives that can affect sales performance and targets. The method used in this study uses a prototype method with a calculation scheme using a remuneration system. Data collection methods using the method of observation, interview methods, and methods of literature. Data analysis uses descriptive analysis. The purpose of this research is expected to help make it easier for companies to get incentive reports accurately and for sales to know clearly how much their incentives are after making lots of sales in real-time and up-to-date. The results of this study are to provide information systems for calculating incentives easily, quickly and accurately making it easier for company management to make decisions and pay incentives more smoothly so as to improve the performance of sales to achieve better sales targets.